2018
DOI: 10.5965/223811711732018531
|View full text |Cite
|
Sign up to set email alerts
|

Índice de área foliar e SPAD durante o ciclo da soja em função da densidade de plantas e sua relação com a produtividade de grãos

Abstract: Índice de área foliar e SPAD durante o ciclo da soja em função da densidade de plantas e sua relação com a produtividade de grãos Leaf area index and SPAD during the soybean development cycle at different plant densities and their relation to grain yield

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
1
9
0
5
Order By: Relevance
“…These data show that soybean growth was lower after wheat than black oat. Yokoyama et al (2018) also observed a lower vegetative growth of soybean plants sown after wheat, compared with corn, Crotalaria spectabilis Roth, and Urochloa ruziziensis (R.Germ. & C.M.Evrard) Morrone & Zuloaga; however, this effect was greatly influenced by the crop season.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…These data show that soybean growth was lower after wheat than black oat. Yokoyama et al (2018) also observed a lower vegetative growth of soybean plants sown after wheat, compared with corn, Crotalaria spectabilis Roth, and Urochloa ruziziensis (R.Germ. & C.M.Evrard) Morrone & Zuloaga; however, this effect was greatly influenced by the crop season.…”
Section: Resultsmentioning
confidence: 78%
“…In addition, the species can be easily desiccated for planting of the subsequent crops (Krenchinski et al, 2018). Another crop that can be used in the autumn/winter season is wheat (Triticum aestivum L.), which has positive effects on soybean growth, compared with corn (Zea mays L.) and fallow (Yokoyama et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of chlorophyll content was quite expressive, with more than one unit of SPAD index reduced for every two-spotted spider mite per cm 2 ( Figure 2). Plants under damage score 4 (28.9 mites per cm 2 ) showed an average SPAD as low as 25.76, far below the level considered ideal for high-grain yield in soybean crops, which is around 40 during growing stages, and 50, during grain filling (Yokoyama et al, 2018). As to the variable grain yield, the regression model indicated a reduction of 0.35 g of grain yield per plant for every two-spotted spider mite per cm 2 (Figure 2).…”
Section: Resultsmentioning
confidence: 90%
“…Durante o ciclo da soja, nas 10 coletas realizadas, não houve efeito da interação entre os tratamentos de entressafra e a adubação nitrogenada na soja sobre os teores de nitrato e amônio no solo, apesar das culturas de entressafra produzirem quantidades distintas de palha, com diferentes características químicas (YOKOYAMA et al, 2018). Na média das cinco repetições o milho sem e com adubação nitrogenada produziu 2,5 e 2,8 t ha -1 de palha, enquanto o trigo, a braquiária e a crotalária produziram 4,7; 3,5 e 0,3 t ha -1 de palha, respectivamente.…”
Section: Resultsunclassified
“…Outra cultura usada na entressafra da soja é o trigo, especialmente em regiões subtropicais ou tropicais com altitudes superiores a 600 m. As culturas de cobertura do solo também são alternativas para o cultivo na entressafra, como as braquiárias (LOSS et al, 2011) e as crotalárias (CARVALHO et al, 2013), objetivando melhorar a qualidade do solo e reduzir problemas fitossanitários. Adicionalmente, em várias regiões do país há ausência de cultivo na entressafra da soja (pousio), provocando aumento da erosão, da degradação da qualidade do solo e da ocorrência de plantas daninhas de difícil controle (MORAES et al, 2013;YOKOYAMA et al, 2018).…”
Section: Introductionunclassified